Planejamento experimental aplicada a um novo separador líquido-líquido utilizado no tratamento de águas residuais contaminadas com petróleo - Fernandes Júnior, Wilaci Eutrópio (2002)
The present work had as objective to apply an experimental planning aiming at to improve the efficiency of separation of a new type of mixer-settler applied to treat waste water contaminated with oil. An unity in scale of laboratory, was installed in the Post-graduation Program of Chemical Engineering of UFRN. It was constructed in partnership with Petrobras S.A. This called device Misturador-Decantador a Inversão de Fases (MDIF) , possess features of conventional mixer-settler and spray column type. The equipment is composed of three main parts: mixing chamber; chamber of decantation and chamber of separation. The efficiency of separation is evaluated analyzing the oil concentrations in water in the feed and the output of the device. For the analysis one used the gravimetric method of oil and greases analysis (TOG). The system in study is a water of formation emulsified with oil. The used extractant is a mixture of Turpentine spirit hydro-carbons, supplied for Petrobras. It was applied, for otimization of the efficiency of separation of the equipment, an experimental planning of the composite central type, having as factorial portion fractionary factorial planning 2 5-2, with the magnifying of the type star and five replications in the central point. In this work, the following independents variables were studied: contents of oil in the feed of the device; volumetric ratio (O/A); total flowrate ; agitation in the mixing chamber and height of the organic bed. Minimum and maximum limits for the studied variables had been fixed according previous works. The analysis of variance for the equation of the empirical model, revealed statistically significant and useful results for predictions ends. The variance analysis also presented the distribution of the error as a normal distribution and was observed that as the dispersions do not depend on the levels of the factors, the independence assumption can be verified. The variation around the average is explained by 98.98%, or either, equal to the maximum value, being the smoothing of the model in relation to the experimental points of 0,98981. The results present a strong interaction between the variable oil contents in the feed and agitation in the mixing chamber, having great and positive influence in the separation efficiency. Another variable that presented a great positive influence was the height of the organic bed. The best results of separation efficiency had been obtained for high flowrates when associates the high oil concentrations and high agitation. The results of the present work had shown excellent agreement with the results carried out through previous works with the mixer-settler of phase inversion